1997
DOI: 10.1002/(sici)1097-0223(199710)17:10<933::aid-pd179>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of trisomy 9: cytogenetic, FISH, and DNA studies

Abstract: A cytogenetic survey and follow-up studies were performed in eight cases of full, mosaic, and pseudomosaic trisomy 9 prenatally diagnosed among 36,213 prenatal samples in our department between August 1970 and July 1996. Besides conventional chromosome analysis, interphase fluorescent in situ hybridization (FISH) was employed. FISH turned out to be a rapid and accurate method for verification of trisomy cell lines and could provide additional information to the prenatal cytogenetic results. FISH also enables t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Most of our cases had the diagnosis of trisomy 9 confirmed further on amniotic fluid or postnatal samples. However, pseudomosaicism or confined placental mosaicism is well recognized with trisomy 915, 20. These conditions are more likely to be found when the original cytogenetic sample is chorionic villi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of our cases had the diagnosis of trisomy 9 confirmed further on amniotic fluid or postnatal samples. However, pseudomosaicism or confined placental mosaicism is well recognized with trisomy 915, 20. These conditions are more likely to be found when the original cytogenetic sample is chorionic villi.…”
Section: Discussionmentioning
confidence: 99%
“…Previous groups have suggested that in every case of trisomy 9 diagnosed on chorionic villi the parents should be counseled regarding the risk of pseudomosaicism or confined placental mosaicism, and offered further fetal analysis by amniocentesis and/or fetal blood sampling and detailed ultrasound assessment15. The uncultured amniocytes or blood lymphocytes can be rapidly analyzed using fluorescent in situ hybridization for chromosome 9 as well as standard culture20. All cases of complete trisomy 9 diagnosed on amniocytes or lymphocytes have been associated with ultrasound anomalies15 and, where relevant, the option of TOP should be offered to the parents.…”
Section: Discussionmentioning
confidence: 99%
“…Of spontaneous abortions caused by autosomal trisomies, approximately 2.2% to 2.7% are due to T9 (Ferreres et al, 2008), and most spontaneously abort (Ferreres et al, 2008; Patil et al, 2012; Pinette et al, 1998). Prenatally reported cases are challenging because cytogenetic abnormalities can be limited to fetal membranes (Pfeiffer et al, 1984; Saura et al, 1995; Sutherland et al, 1976), and it may be difficult to distinguish between generalized and placental mosaicism (Van den Berg et al, 1997). Additionally, many individuals with T9 were diagnosed on limited cell numbers and/or did not have additional confirmatory tissue, so low‐level mosaicism may not be excluded (Cantú et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…More than 50 cases have been reported, most of which were diagnosed after birth. As cases diagnosed prenatally usually culminate in induced abortions [14], the natural history of fetuses with trisomy 9 mosaicism remains unknown. We report three cases of trisomy 9 mosaicism diagnosed in utero with ongoing pregnancies.…”
Section: Introductionmentioning
confidence: 99%